Heating Characteristics of Films Prepared with Polymer-Graphite Composites - Seojin Kim; Weontae Oh; Jong-Seong Bae; Seong Baek Yang; Jeong Hyun Yeum; Jaehyeung Park; Choonghyun Sung; Jungsoo Kim; Jae-Cheon Shin (International Journal of Polymer Science)
Heating films were prepared by using poly(methyl methacrylate) and polybutadiene composites containing graphite. The heating film was prepared by casting the as-made polymer composite on the PET film. Copper electrodes were attached to both ends of the as-prepared film, and the heating characteristics of the film were analyzed while applying the DC voltage. The electrical conductivity and the heating temperature of the heating films depended on the size, the structure, the content, and the dispersion characteristics of the graphite in the composite. The electrical resistance of the heating film was controlled to adjust the heating temperature of the film. The relationship between the physical/chemical structure and the heating characteristics of the composite film was studied by measuring the heating temperature as functions of film thickness and resistance by using an infrared thermal imaging camera. The lower the film resistance, the higher the heating temperature of the film. The surface temperature was uniform throughout the film.